Harry Potter and the goblet of fire - Newell, Mike, 1942; Heyman, David; Radcliffe, Daniel, 1989; Grint, Rupert, 1988; Warner Bros. Pictures; Heyday Films; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
As Harry enters his fourth year at Hogwarts Academy, he is mysteriously entered in the Triwizard Tournament which challenges his wizarding skills, friendships, and character amid signs that an old enemy is growing stronger
Title from title screen
Director of photography, Roger Pratt ; production design, Stuart Craig ; visual effects supervisor, Jim Mitchell ; special visual effects and animation, Industrial Light & Magic ; editor, Mick Audsley ; music, Patrick Doyle ; screenplay by Steve Kloves
Casts: Daniel Radcliffe, Rupert Grint, Emma Watson, Robbie Coltrane, Ralph Fiennes, Michael Gambon, Brendan Gleeson, Jason Isaacs, Gary Oldman, Miranda Richardson, Alan Rickman, Maggie Smith
In English or Spanish with optional English, French, or Spanish subtitles
Keywords: Wizards -- Drama; Magic -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Drama